A RARE CLINICAL CASE OF SIMULTANEOUS DEVELOPMENT OF ECTOPIC AND UTERINE PREGNANCY AFTER ART - Fetishcheva, Larisa Egorovna; Elgina, Svetlana Ivanovna; Rudaeva, Elena Vladimirovna; Moses Кира; Moses, Vadim Gelievich; Chernykh, Natalya Stepanovna (Mother and Baby in Kuzbass, 2026)
The article describes a clinical case of heterotopic pregnancy, which is the simultaneous development of both intrauterine and ectopic pregnancies, and is an extremely rare complication of IVF. Heterotopic pregnancy is a relatively rare condition in obstetric and gynecological practice. It poses a significant risk to a woman’s reproductive health, including the potential for bleeding and even death. Among the various types of heterotopic pregnancy, the combination of intrauterine and tubal localization is the most common. The article explores the challenges in diagnosing this condition. Transvaginal ultrasound is the most informative and allows for the visualization of the ovum in the early stages of pregnancy. Therapeutic approaches for this type of pathology are also discussed.